2022
DOI: 10.1111/csp2.12784
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural mobile game evaluation shows improvement in environmental learning, but not behavior

Abstract: Games have a wide range of potential uses, from mediating conservation conflicts to changing behaviors. However, there have been few impact evaluations of serious games published in the environmental field. We conducted the first cross-cultural evaluation of an environmental mobile game, Save The Purple Frog. In a randomized control trial with both UK and Indian participants, we found very strong evidence that Save The Purple Frog had a positive impact on learning (effect size 0.62, p = 0.0001), but no evidenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Academics (or pracademics) can advise on relevant theory and research and how to incorporate formal theory into programmes (with support for evaluation at conclusion). Examples of partnering and theory advising exist in social marketing ranging from prevention of substance use, sexual risk and violence (Andrade et al , 2018; Yoshihama et al , 2012), energy conservation (Bator et al , 2014, 2019), equity-oriented parenting (Pluye et al , 2015, 2020), lead reduction (Khaliq et al , 2021), childhood obesity (Gadsby et al , 2020), policy development (Bryant et al , 2014), to biodiversity conservation (Thomas-Walters et al , 2020; Thomas‐Walters and Veríssimo, 2022).…”
Section: Recommendationsmentioning
confidence: 99%
“…Academics (or pracademics) can advise on relevant theory and research and how to incorporate formal theory into programmes (with support for evaluation at conclusion). Examples of partnering and theory advising exist in social marketing ranging from prevention of substance use, sexual risk and violence (Andrade et al , 2018; Yoshihama et al , 2012), energy conservation (Bator et al , 2014, 2019), equity-oriented parenting (Pluye et al , 2015, 2020), lead reduction (Khaliq et al , 2021), childhood obesity (Gadsby et al , 2020), policy development (Bryant et al , 2014), to biodiversity conservation (Thomas-Walters et al , 2020; Thomas‐Walters and Veríssimo, 2022).…”
Section: Recommendationsmentioning
confidence: 99%
“…Another relevant line of technology is serious games. These games are not intended to entertain but can play a prominent role in the process of informing, educating, and promoting behavior change in terms of environmental sustainability (Ong & Araral, 2022;Thomas-Walters & Veríssimo, 2022). According to studies, playing games can help people become more environmentally aware, foster eco-friendly attitudes, and encourage individuals to adopt pro-environmental behaviors (e.g., Dunn and Veríssimo, 2021;Orland et al, 2014).…”
Section: Communicationmentioning
confidence: 99%
“…Games are able to do so because they provide a fun, engaging, and low-pressure environment where players can experiment with different actions and see the consequences of their choices. However, some empirical studies of serious games have found no significant impact on attitudes and behavior but a significant effect on learning (e.g., Thomas-Walters & Veríssimo, 2022). Thus, the advent of these persuasive technologies creates a new area for the research and application of social marketing programs that must be addressed in the near future.…”
Section: Communicationmentioning
confidence: 99%